Study of feasible fuel additive on reducing ic engine exhaust emission and impriving engine performance - Chan, Chung Kiet (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Effects of fuel oxygenate on the diesel engine performance and exhaust emission were investigated by running the compression ignition engine with methanol diesel fuel blend. Investigation has been done on the effects of the increase of oxygen content in diesel fuel to engine performance and exhaust emission. In this fmal year project, four blends of methanol diesel fuel blend are prepared with 2%, 4%, 6%, and 8% oxygen content respectively. Engine performance experiment has been conducted by using single cylinder, direct injection and water cooled diesel engine. While the exhaust emission test is done by using the flue gas analyser. The results of using methanol diesel fuel blend show that there were increases of brake specific fuel consumption for about 5.74% to 18.75%. Effectiveness of methanol diesel fuel blend in the Carbon Monoxide, CO emissions reduction where the CO emissions are reduced in the range of3.96% to 15.82%. Oxides of nitrogen, NOx increase with the increasing amount of oxygen in the methanol diesel fuel blend. The NOx formation has increased by 8.33% - 23.37% when using methanol diesel fuel blend with 2%, 4%, 6% and 8% oxygen content. For the Fourier Transform Infrared Ray (FTIR) analysis shows the addition of methanol into diesel fuel only adds the O-H bonds into the diesel fuel. The addition of methanol will not cause any chemical reaction and produce other products. It was concluded that, methanol is an effective fuel oxygenates for diesel fuel for improving engine performance and exhaust emission.